Seasonal Dynamics of Changes in the Freezing Point of Natural Milk as a Criterion for Determining the Possible Amount of Added Water - Rusko, Nataliia; Ponomarova, Valeriia; Korkh, Igor; Paliy, Anatoliy (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):298